2013
DOI: 10.1108/ijmhsc-05-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

“Solving Tension”: coping among Bhutanese refugees in Nepal

Abstract: PurposeThe Bhutanese refugee camps of eastern Nepal are home to a mass resettlement operation; over half the population has been relocated within the past five years. While recent research suggests Bhutanese refugees are experiencing degradation of social networks and rising suicide rates, little is known about ethnocultural pathways to coping and resilience in this population.Design/methodology/approachA common coping measure (Brief COPE) was adapted to the linguistic and cultural context of the refugee camps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 25 publications
4
47
0
Order By: Relevance
“…Studies were published between 2002 and 2018. Four were quantitative cross sectional designs (Chase, Welton‐Mitchell, & Bhattarai, ; Emmelkamp, Komproe, Van Ommeren, & Schagen, ; Nakash, Nagar, Shoshani, & Lurie, ; Segal, Khoury, Salah, & Ghannam, ), 10 were qualitative studies (Akinyemi, Owoaje, & Cadmus, ; Chase & Sapkota, ; Cohen & Asgary, ; Elsass & Phuntsok, ; Hussain & Bhushan, ; Khawaja et al, ; Labys, Dreyer, & Burns, ; Lavie‐Ajayi & Slonim‐Nevo, ; Pavlish, ; Tippens, ) and two were mixed methods studies. From the mixed methods studies only the qualitative data were extracted for this review due to the quantitative components focusing solely on barriers (Chemali, Borba, Johnson, Khair, & Fricchione, ; Muhwezi & Sam, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies were published between 2002 and 2018. Four were quantitative cross sectional designs (Chase, Welton‐Mitchell, & Bhattarai, ; Emmelkamp, Komproe, Van Ommeren, & Schagen, ; Nakash, Nagar, Shoshani, & Lurie, ; Segal, Khoury, Salah, & Ghannam, ), 10 were qualitative studies (Akinyemi, Owoaje, & Cadmus, ; Chase & Sapkota, ; Cohen & Asgary, ; Elsass & Phuntsok, ; Hussain & Bhushan, ; Khawaja et al, ; Labys, Dreyer, & Burns, ; Lavie‐Ajayi & Slonim‐Nevo, ; Pavlish, ; Tippens, ) and two were mixed methods studies. From the mixed methods studies only the qualitative data were extracted for this review due to the quantitative components focusing solely on barriers (Chemali, Borba, Johnson, Khair, & Fricchione, ; Muhwezi & Sam, ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted in various ( n = 11) host countries including three studies in Nepal (Chase & Sapkota, ; Chase et al, ; Emmelkamp et al, ) (Chase & Sapkota, ; Chase et al, ; Emmelkamp et al, ), two in Lebanon (Chemali et al, ; Segal et al, ), two in India (Elsass & Phuntsok, ; Hussain & Bhushan, ), and two in Israel (Lavie‐Ajayi & Slonim‐Nevo, ; Nakash et al, ). Studies were also conducted in Nigeria (Akinyemi et al, ), Thailand (Cohen & Asgary, ), Australia (retrospectively focused on coping during transit period in other host countries) (Khawaja et al, ), South Africa (Labys et al, ), Uganda (Muhwezi & Sam, ), Rwanda (Pavlish, ), and Kenya (Tippens, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to cultural assimilation barriers, refugees experience a devaluation of their professional skills and face subsequent economic challenges both in refugee camps (where they are not permitted to work) and after migration where language skills and institutional barriers must be overcome before employment is viable. Chase et al, found that Bhutanese refugees preferred to cope independently and tended to blame themselves for failures [51, 52]. Additionally, findings from Sri Lanka suggest that suicides are understood and used as performative acts of protest or retaliation, often following family conflict [44, 53].…”
Section: Discussionmentioning
confidence: 99%